Social Structures and Income Distribution in Colonial sub-Saharan Africa: The case of Bechuanaland Protectorate, 1936-1964 - Jutta Bolt; Ellen Hillbom (African Economic History Network (AEHN), 2013)
In this paper we estimate the level and inequality of income for Bechuanaland Protectorate by constructing four social tables between 1936 to 1964 using colonial archives and anthropological records. We present a working hypothesis that there is need to further analyze Botswana's colonial era if we are to understand several aspects of contemporary economic structures. Our focus is on identifying the roots of post-independence high levels of inequality. We find that first of all that migrant labour to neighbouring South Africa earned well relative to domestic labour in the Protectorate, both in the formal and traditional sectors. Remittances their families back home and became an important strategy for the poorer segments of society to stay at or above subsistence. Second, the creation of a beef export sector in the 1930s brought with it new opportunities to access export incomes and starting in the 1940s this led to increasing income inequalities and a polarization in cattle holdings. Third, wages for government officials were forging ahead creating an increasing income divide between public and private formal employment. In conclusion we infer that Botswana's contemporary institutional inequality has far reaching historical roots.
Keywords: N17; N37; N57; 330; Africa; Bechuanaland; social tables; inequality